2019
DOI: 10.1021/acs.energyfuels.9b03000
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Evaluation of Surfactant-Nanoparticles Foam for Enhanced Oil Recovery under High Temperature

Abstract: In this article, experiments and simulations were conducted to evaluate performance of surfactant-nanoparticles foam for enhanced oil recovery under high temperature. Experimentally, the displacement behavior of surfactant-nanoparticles foam for enhanced oil recovery was studied by micromodel tests at 90 °C. The recovery performance of surfactant-nanoparticles foam flooding was analyzed by sandpack flooding experiments at 150 °C. Theoretically, a mechanistic model of surfactant-nanoparticles foam flooding was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…They found that foam injection in layered media successfully diverted gas from a high permeable fracture to a low permeable matrix . Nanoparticle induced foam, , polymer enhanced foam and self-generated heat foam were also investigated by 2D glass micromodels.…”
Section: Application In Oil and Gas Recoverymentioning
confidence: 99%
“…They found that foam injection in layered media successfully diverted gas from a high permeable fracture to a low permeable matrix . Nanoparticle induced foam, , polymer enhanced foam and self-generated heat foam were also investigated by 2D glass micromodels.…”
Section: Application In Oil and Gas Recoverymentioning
confidence: 99%
“…Alvarez et al studied the adsorption of silica particles at the interfaces of various systems and confirmed that the interfacial tension of the system decreased upon increasing the particle concentration. Lu et al confirmed that mixing FRC-1 foam with nanoparticles displayed excellent stability and displacement. Hu et al studied the injection and displacement effects of nanoparticles in tight oil reservoir environments, and the efficiency of crude oil production increased significantly.…”
Section: Introductionmentioning
confidence: 96%
“…The microflow behavior and the recovery performance of aqueous CO 2 -foam stabilized by particulate matter (PM) from coal combustion has been also studied using a glass-based microfluidic device . Micromodels have recently been applied to compare the recovery performance of foam injection with that of waterflood and steam flood processes, showing improvements in sweep efficiency and porescale recovery factor. , While the majority of the previous microfluidics foam studies provides insight into the foam application for conventional enhanced oil recovery, for thermal extraction processes such as foam-SAGD, it is essential to evaluate the performance of foam agents at relevant reservoir operating temperatures (i.e., >150 °C): the condition where the fluid incompatibility can result in serious reservoir damage, surfactant thermal instability, and overall process inefficiency.…”
Section: Introductionmentioning
confidence: 99%